A glass-ceramic energy storage ceramic material for LTCC and a preparation method thereof

By using alkaline earth metal oxides and other oxide raw materials, combined with ball milling and annealing crystallization treatment, microcrystalline glass energy storage ceramic materials with high dielectric constant, high breakdown strength and high energy storage density were prepared, solving the problems of low energy storage density and poor thermal stability of existing dielectric glass ceramic materials.

CN118084332BActive Publication Date: 2025-03-04JIANGSU FREETEL COMM CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410188981.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2025-03-04
Estimated Expiration
2044-02-20

AI Technical Summary

Technical Problem

The existing dielectric glass ceramic materials have low breakdown strength, poor thermal stability and low energy storage density, making it difficult to meet the needs of high power density and fast charging and discharge.

Method used

Using alkaline earth metal oxides, SrO, Na2O, Nb2O5 and SiO2 as raw materials, microcrystalline glass energy storage ceramic materials with high dielectric constant, high breakdown strength and high energy storage density were prepared by ball milling and annealing crystallization treatment.

Benefits of technology

The energy storage density, dielectric constant and breakdown strength of microcrystalline glass energy storage ceramic materials are significantly improved, and the temperature stability is improved, solving the problems of low energy storage density and poor thermal stability of existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118084332B_ABST
    Figure CN118084332B_ABST
Patent Text Reader

Abstract

The present invention discloses a microcrystalline glass energy storage ceramic material for LTCC and a preparation method thereof, belonging to the technical field of electronic information ceramics. The material comprises the following raw materials in weight percentage: 2-5% alkaline earth metal oxide, 30-40% SrO, 20-40% SiO2, 5-10% Na2O and 20-30% Nb2O5; the preparation method comprises the following steps: (1) ball milling the raw materials after mixing, and drying to obtain a mixed powder; (2) melting the obtained mixed powder, then casting, annealing, and finally annealing and crystallizing to obtain. The present invention combines the traditional melting method with casting molding to prepare microcrystalline glass with high dielectric constant, high breakdown strength and high energy storage density. The preparation process is simple, the stability is good and the cost is low, it is suitable for mass production, and has industrial significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic information ceramics, and in particular to a glass-ceramic energy storage ceramic material for LTCC and a preparation method thereof. Background Art

[0002] Dielectric capacitors have significant characteristics such as high power density and ultrafast charging and discharging, and have been widely used in pulse power fields such as controlled nuclear fusion, high-power lasers, electromagnetic railguns and phased array radars. With the continuous development of the miniaturization trend of electronic devices, people are in urgent need of dielectric materials with high energy storage density to manufacture energy storage capacitors.

[0003] Traditional ceramic materials, despite their versatility, have limited breakdown strength due to internal porosity defects. Organic polymer materials, while offering certain advantages, have low dielectric constants and poor temperature stability. In contrast, glass-ceramics are a composite material characterized by the coexistence of glass and ceramic phases. This composition is achieved through a melting and high-temperature crystallization process, where a dense ceramic phase is precipitated in a glass matrix. This deliberate structural design is designed to improve breakdown strength while maintaining a specific dielectric constant. As a result, glass-ceramics, positioned as capacitor dielectric materials, have great potential in the field of pulsed power. The combination of glass and ceramic components, achieved through careful processing, not only enhances the material's breakdown strength but also ensures that it meets the necessary dielectric constant. This dual enhancement makes glass-ceramics an ideal choice for advancing pulsed power applications.

[0004] At present, the main dielectric glass ceramics are mainly divided into titanate glass ceramics and niobate glass ceramics. Titanate glass ceramics are prone to dendrite precipitation. The presence of dendrites will lead to the inhomogeneity of the crystal phase distribution and glass matrix inside the glass ceramics, resulting in a decrease in the breakdown strength of the glass ceramics. In contrast, niobate glass ceramics exhibit a denser microstructure and good dielectric properties, but niobate glass ceramics still have problems such as poor temperature stability. Therefore, it is of great significance to invent a microcrystalline glass energy storage material with a stable dielectric constant, good thermal stability and high energy storage density. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a microcrystalline glass energy storage ceramic material for LTCC and a preparation method thereof, so as to solve the problems of low breakdown strength, poor thermal stability and low energy storage density of existing dielectric glass ceramics.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A glass-ceramic energy storage ceramic material for LTCC, comprising the following raw materials in percentage by weight:

[0008] 2-5% alkaline earth metal oxides, 30-40% SrO, 20-40% SiO2, 5-10% Na2O and 20-30% Nb2O5.

[0009] The beneficial effects of the present invention are as follows: the present invention uses alkaline earth metal oxides, SrO, Na2O, Nb2O5 and SiO2 as raw materials to prepare microcrystalline glass energy storage ceramic materials, and effectively improves the energy storage density, dielectric constant, breakdown strength and temperature stability of the microcrystalline glass energy storage ceramic materials by producing crystal phase structures such as the main crystal phase SrNb2O6, thereby solving the problems of low dielectric constant and poor temperature stability of LTCC ceramic materials in the existing microcrystalline glass system.

[0010] Further, the following raw materials are included in weight percentage:

[0011] 3% alkaline earth metal oxides, 33% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5.

[0012] Further, the alkaline earth metal oxide includes at least one of MgO and CaO.

[0013] The method for preparing the above-mentioned microcrystalline glass energy storage ceramic material for LTCC comprises the following steps:

[0014] (1) mixing alkaline earth metal oxide, SrO, SiO2, Na2O and Nb2O5, ball milling and drying to obtain a mixed powder;

[0015] (2) The mixed powder obtained in step (1) is melted, molded, annealed, and finally annealed and crystallized to obtain.

[0016] The beneficial effects of the present invention are as follows: the present invention combines the traditional melting method with the casting molding process, and further performs annealing crystallization treatment after annealing treatment, and successfully prepares microcrystalline glass with high dielectric constant, high breakdown strength and high energy storage density. The preparation process is simple, stable and low in cost, suitable for mass production, and has industrial significance.

[0017] Furthermore, in step (1), the raw materials are mixed in a mixer at a speed of 20-40 r / min for 30-60 min; after mixing, the raw materials are sieved using a 40-60 mesh screen.

[0018] Furthermore, the ball milling conditions in step (1) are as follows: the mass ratio of the raw material powder, agate balls and deionized water is 1:3-5:3-4, and the ball milling time is 16-28 hours.

[0019] Preferably, the ball milling conditions in step (1) are as follows: the mass ratio of raw material powder, agate balls and deionized water is 1:4:3.5, and the ball milling time is 20 hours.

[0020] Furthermore, the ball milling adopts a rolling ball milling.

[0021] The beneficial effect of adopting the above further technical solution is that the present invention processes powders by combining mixing and stirring + rolling ball milling, thereby ensuring the uniformity of mixing and the consistency of powder particle size.

[0022] Furthermore, in step (1), the drying temperature is 98-110° C. and the drying time is 8-24 h.

[0023] Preferably, the drying temperature in step (1) is 105° C. and the drying time is 15 h.

[0024] Furthermore, after drying, the powder is sieved with a 40-60 mesh screen to obtain a powder with a particle size less than 2 μm.

[0025] The beneficial effect of adopting the above further technical solution is that the present invention ensures the consistency of the particle size of the obtained powder through two screening processes before ball milling and after drying, and avoids the influence of large volume powder on subsequent processing.

[0026] Furthermore, the melting conditions in step (2) are: firstly heating to 1000-1100°C in 100-150 minutes, then heating to 1450-1650°C in 80-120 minutes, and keeping the temperature for 2-4 hours.

[0027] Preferably, the melting conditions in step (2) are: firstly heating to 1050°C within 125 minutes, then heating to 1550°C within 100 minutes, and keeping the temperature for 3 hours.

[0028] Furthermore, in step (2), the discharge temperature of the casting mold is 550-650° C., and the interval time between the casting mold and the annealing treatment is less than or equal to 3 minutes.

[0029] Preferably, the discharge temperature of the casting mold in step (2) is 600°C.

[0030] Furthermore, in step (2), the mold of the casting mold is heated to 550-650° C. in advance, and the heating rate is 3-5° C. / min.

[0031] Furthermore, in step (2), the annealing temperature is 550-650°C, and the annealing rate is 80-120°C / 24h.

[0032] Preferably, the temperature of the annealing treatment in step (2) is 600° C., and the rate of the annealing treatment is 100° C. / 24 h.

[0033] Furthermore, the muffle furnace for annealing treatment in step (2) is heated to 550-650°C in advance, and the heating rate is 2-6°C / min.

[0034] Furthermore, after the annealing treatment, the obtained glass is cut, ground and polished to obtain the required size.

[0035] The beneficial effect of adopting the above further technical scheme is: the present invention successfully produces glass with a smooth surface and dense structure through powder melting, molding and annealing treatment, which is convenient for subsequent annealing and crystallization treatment to prepare microcrystalline glass energy storage ceramic materials.

[0036] Furthermore, in step (2), the temperature of the annealing and crystallization treatment is 800-1200° C., and the time of the annealing and crystallization treatment is 3-6 hours.

[0037] Preferably, the temperature of the annealing and crystallization treatment in step (2) is 1100° C., and the time of the annealing and crystallization treatment is 4.5 h.

[0038] The beneficial effects of adopting the above-mentioned further technical scheme are as follows: the present invention studies the correlation between dielectric properties and crystal phases by annealing and crystallizing the annealed glass, and finds that with the increase of annealing and crystallization temperature, the microstructure of the microcrystalline glass will change from a dense structure to a large number of defective structures. When the annealing and crystallization temperature is 1100°C, the obtained microcrystalline glass has the highest energy storage density, higher dielectric constant and breakdown strength, and has obvious dielectric constant stability and good thermal stability compared to traditional ceramics.

[0039] The present invention has the following beneficial effects:

[0040] (1) The present invention combines the traditional melting method with casting molding to prepare microcrystalline glass with high dielectric constant, high breakdown strength and high energy storage density. The preparation process is simple, the stability is good and the cost is low. It is suitable for mass production and has industrial significance.

[0041] (2) The present invention prepares a microcrystalline glass energy storage ceramic material by annealing and crystallizing the glass obtained by annealing, and obtains a microcrystalline glass energy storage ceramic material with an energy storage density of 2.87 J / cm at an annealing and crystallization temperature of 1100°C. 3 , dielectric constant of 280, breakdown strength of 481kV / cm. It solves the problems of low dielectric constant and poor temperature stability of LTCC ceramic materials in the existing microcrystalline glass system, and can be widely used in the field of electronic information; compared with traditional ceramics, it has a more stable dielectric constant and better thermal stability, and is expected to become a dielectric material used in pulse power systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1XRD diagrams of glass-ceramic energy storage ceramic materials obtained in Example 1 and Examples 6-9;

[0043] Figure 2 The dielectric properties experimental results of the glass-ceramic energy storage ceramic materials obtained in Example 1 and Examples 6-9 at different frequencies and temperatures are shown in Figure 1, where (a) is for different frequencies and (b) is for different temperatures.

[0044] Figure 3 The dielectric constant, breakdown strength and energy storage density results of the microcrystalline glass energy storage ceramic materials obtained in Examples 1 and 6-9 are shown in FIG. DETAILED DESCRIPTION

[0045] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] Embodiment 1:

[0047] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0048] (1) Weigh the raw materials according to the following mass percentages: 3% CaO, 33% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 30 r / min for 45 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0049] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:3.5 for ball milling for 20 hours using a rolling ball mill.

[0050] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0051] (4) The mixed powder obtained in step (3) is placed in a melting furnace for melting at a temperature of 1550° C. and kept warm for 3 hours.

[0052] (5) The mold is heated to 600° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 600° C.

[0053] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 600° C. at a heating rate of 4° C. / min for annealing at a rate of 100° C. / 24 h.

[0054] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0055] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. for 4.5 h to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0056] Embodiment 2:

[0057] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0058] (1) Weigh the raw materials according to the following mass percentages: 3% MgO, 33% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 40 r / min for 30 min to fully mix the raw materials, and then sieve them with a 40-mesh sieve.

[0059] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:4 for ball milling for 24 hours using a rolling ball mill.

[0060] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 40-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0061] (4) The mixed powder obtained in step (3) is placed in a melting furnace for melting at a melting temperature of 1650° C. and kept warm for 2 h.

[0062] (5) The mold is heated to 650° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 650° C.

[0063] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 650° C. at a heating rate of 4° C. / min for annealing at a rate of 110° C. / 24 h.

[0064] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0065] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. for 4.5 h to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0066] Embodiment 3:

[0067] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0068] (1) Weigh the raw materials according to the following mass percentages: 5% MgO, 33% SrO, 32% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 30 r / min for 45 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0069] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:4 for ball milling for 20 hours using a rolling ball mill.

[0070] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0071] (4) The mixed powder obtained in step (3) is placed in a smelting furnace for melting at a melting temperature of 1450° C. and kept warm for 4 hours.

[0072] (5) The mold is heated to 550° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 550° C.

[0073] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 550° C. at a heating rate of 4° C. / min for annealing at a rate of 90° C. / 24 h.

[0074] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0075] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. for 4.5 h to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0076] Embodiment 4:

[0077] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0078] (1) Weigh the raw materials according to the following mass percentages: 4% CaO, 33% SrO, 33% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 30 r / min for 45 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0079] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:3 for ball milling for 20 hours using a rolling ball mill.

[0080] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0081] (4) The mixed powder obtained in step (3) is placed in a smelting furnace for melting at a temperature of 1500° C. for 3 hours.

[0082] (5) The mold is heated to 650° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 650° C.

[0083] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 650° C. at a heating rate of 4° C. / min for annealing at a rate of 100° C. / 24 h.

[0084] (7) Cutting, grinding and polishing the annealed product of step (6) to obtain a glass sample. (8) Annealing and crystallizing the glass sample obtained in step (7) at 1100° C. for 4.5 hours to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0085] Embodiment 5:

[0086] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0087] (1) Weigh the raw materials according to the following mass percentages: 2% CaO, 2% MgO, 33% SrO, 33% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding. The mixer speed is 25 r / min for 60 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0088] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:3 for ball milling for 20 hours using a rolling ball mill.

[0089] (3) The product after ball milling in step (2) was placed in an oven at 110° C. and dried for 12 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0090] (4) The mixed powder obtained in step (3) is placed in a smelting furnace for melting at a temperature of 1600° C. and kept warm for 2.5 hours.

[0091] (5) The mold is heated to 600° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 600° C.

[0092] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 600° C. at a heating rate of 4° C. / min for annealing at a rate of 100° C. / 24 h.

[0093] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0094] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. for 4.5 h to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0095] Embodiment 6-9:

[0096] A method for preparing a microcrystalline glass energy storage ceramic for LTCC, the preparation method is the same as that of Example 1, except that the annealing crystallization temperature in step (7) is modified to 800°C, 900°C, 1000°C and 1200°C respectively, and the other steps remain unchanged.

[0097] Comparative Example 1:

[0098] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0099] (1) Weigh the raw materials according to the following mass percentages: 36% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 30 r / min for 45 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0100] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:3.5 for ball milling for 20 hours using a rolling ball mill.

[0101] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0102] (4) The mixed powder obtained in step (3) is placed in a melting furnace for melting at a temperature of 1550° C. and kept warm for 3 hours.

[0103] (5) The mold is heated to 600° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 600° C.

[0104] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 600° C. at a heating rate of 4° C. / min for annealing at a rate of 100° C. / 24 h.

[0105] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0106] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. for 4.5 h to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0107] Comparative Example 2:

[0108] A method for preparing glass-ceramic energy storage ceramics for LTCC comprises the following steps:

[0109] (1) Weigh the raw materials according to the following mass percentages: 3% BaO, 33% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5, and then pour them into a mixer for mixing and grinding at a mixer speed of 30 r / min for 45 min to fully mix the raw materials, and then sieve them with a 50-mesh sieve.

[0110] (2) The sieved raw material in step (1) is placed in a nylon ball mill with agate balls and deionized water in a mass ratio of 1:4:3.5 for ball milling for 20 hours using a rolling ball mill.

[0111] (3) The product after ball milling in step (2) was placed in an oven at 105° C. and dried for 15 h, and then sieved with a 50-mesh sieve to obtain a mixed powder with a particle size of less than 2 μm.

[0112] (4) The mixed powder obtained in step (3) is placed in a melting furnace for melting at a temperature of 1550° C. and kept warm for 3 hours.

[0113] (5) The mold is heated to 600° C. at a heating rate of 4° C. / min, and then the molten product of step (4) is poured into the mold to form a block of glass, ensuring that the discharge temperature is 600° C.

[0114] (6) Within 3 minutes, the glass formed in step (5) is placed in a muffle furnace that has been heated to 600° C. at a heating rate of 4° C. / min for annealing at a rate of 100° C. / 24 h.

[0115] (7) Cutting, grinding and polishing the annealing product of step (6) to obtain a glass sample.

[0116] (8) The glass sample obtained in step (7) is annealed and crystallized at 1100° C. to obtain a microcrystalline glass energy storage ceramic for LTCC.

[0117] Experimental Example 1: Performance Characterization of Glass-ceramics Energy Storage Ceramics Prepared at Different Annealing Crystallization Temperatures

[0118] The glass-ceramic energy storage ceramics prepared in Example 1 and Examples 6-9 were used for experiments.

[0119] (1) XRD diffraction experiment

[0120] XRD diffraction analysis was used to test the crystal phase of the sample. The experimental results are as follows: Figure 1 shown.

[0121] According to the comparison of the standard cards, the microcrystalline glass energy storage ceramic samples prepared in Example 1 and Examples 6-9 all showed crystalline phases of SrNb2O6, Sr6Nb 10 O 30 、NaSr2Nb5O 15 The experimental results show that with the increase of crystallization temperature, the main crystal phase changes from SrNb2O6 to NaNbO3 and Sr6Nb 10 O 30 The change in the dielectric constant of the material is related to the content of these two crystalline phases. The increase in crystallization temperature will cause significant changes in the microstructure, transforming the dense structure into a structure characterized by a large number of defects, thus changing the dielectric properties of the material.

[0122] (2) Dielectric properties test

[0123] The samples were tested using an impedance analyzer. Before the test, silver electrodes with a diameter of 6 mm were coated on both sides of the samples and dried at 120°C for 4 hours. The experimental results are as follows: Figure 2 shown.

[0124] It can be seen from the figure that with the increase of annealing crystallization temperature, the dielectric constant of the sample shows an upward trend. At 1000°C, the dielectric constant is relatively small, about 40. At 1100°C, the dielectric constant rises significantly, reaching 280. When the annealing crystallization temperature is 1200°C, the dielectric constant rises to about 500. In addition, the dielectric constants of the samples at 1100°C and 1200°C have a significant downward trend with the increase of frequency; when the test frequency is 10kHz, the dielectric properties of the material do not change significantly with temperature, indicating that the temperature has little effect on the dielectric properties of the sample, indicating that the microcrystalline glass energy storage ceramics prepared by the present invention have good temperature stability.

[0125] (3) Breakdown strength and energy storage density test

[0126] The breakdown strength test is analyzed in a vacuum using a breakdown voltage detector. The test fixture of the breakdown voltage detector consists of a high-voltage device and electrodes. Two electrodes with a diameter of 25 mm are immersed in silicone oil. The sample is placed between the two electrodes to ensure that the sample does not contact the reactive gas, and then the electrode voltage is gradually increased until the sample breaks down. Before the test, silver electrodes with a diameter of 6 mm are coated on both sides of the sample and dried at 120°C for 4 hours.

[0127] The test method for energy storage density is:

[0128] Glass ceramics are linear media, and their hysteresis loop is usually a straight line. For linear dielectrics, the energy storage density, dielectric constant and breakdown strength are linearly related, and can be calculated using the following formula:

[0129]

[0130] Where ε0 is the dielectric constant of vacuum, ε r is the relative dielectric constant, E b is the breakdown field strength.

[0131] The experimental results are as follows Figure 3 shown.

[0132] Figure 3 The dielectric constant, breakdown strength and energy storage density of microcrystalline glass energy storage ceramics prepared at different annealing crystallization temperatures are shown. According to the results, the breakdown strength of the microcrystalline glass energy storage ceramics decreases gradually with the increase of the annealing crystallization temperature, and the energy storage density first increases and then decreases with the increase of the annealing crystallization temperature. When the annealing crystallization temperature is 1100°C, the prepared microcrystalline glass energy storage ceramics (ie, Example 1) exhibits the highest energy storage density, higher dielectric constant and breakdown strength, and is the embodiment with the best comprehensive performance of the present invention.

[0133] Experimental Example 2: Performance Characterization of Glass-ceramics Energy Storage Ceramics Made from Different Raw Material Compositions

[0134] The glass-ceramic energy storage ceramics prepared in Examples 1-5 and Comparative Examples 1-2 were used for experiments. The dielectric properties, breakdown strength and energy storage density thereof were tested using the test method in Example 1. The experimental results are shown in Table 1 below.

[0135] Table 1 Performance parameters of glass-ceramics energy storage ceramics made from different raw material components

[0136]

[0137] According to the data in Table 1 above, the dielectric constant, breakdown strength and energy storage density of the microcrystalline glass energy storage ceramics prepared in Examples 1-5 of the present invention are significantly higher than those of Comparative Example 1 without adding MgO or CaO and Comparative Example 2 using BaO as a substitute. Among them, the comprehensive performance of Example 1 is better, and the performance of Examples 2 and 3 using CaO as the alkaline earth metal oxide is better than that of Examples 2 and 3 using MgO as the metal oxide.

[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A glass-ceramic energy storage ceramic material for LTCC, characterized in that: The following raw materials are included in weight percentage: 3% alkaline earth oxides, 33% SrO, 34% SiO2, 8% Na2O and 22% Nb2O5; Wherein, the alkaline earth metal oxide includes at least one of MgO and CaO; The above-mentioned microcrystalline glass energy storage ceramic material is prepared by the following method: (1) Alkaline earth metal oxides, SrO, SiO2, Na2O and Nb2O5 are mixed, ball-milled and dried to obtain a mixed powder; (2) melting the mixed powder obtained in step (1), casting it into a mold, annealing it, and finally subjecting it to annealing and crystallization to obtain; Wherein, the drying temperature in step (1) is 98-110°C and the drying time is 8-24 h; The melting conditions in step (2) are: firstly heating to 1000-1100°C in 100-150 min, then heating to 1450-1650°C in 80-120 min, and keeping the temperature for 2-4 h; The annealing temperature in step (2) is 550-650°C, and the annealing rate is 80-120°C / 24 h; The temperature of the annealing and crystallization treatment in step (2) is 800-1200°C, and the time of the annealing and crystallization treatment is 3-6 h.

2. The glass-ceramic energy storage ceramic material for LTCC according to claim 1, characterized in that: The ball milling conditions in step (1) are as follows: the mass ratio of raw material powder, agate balls and deionized water is 1:3-5:3-4, and the ball milling time is 16-28 h.

3. The glass-ceramic energy storage ceramic material for LTCC according to claim 1, characterized in that: In the step (2), the discharge temperature of the casting mold is 550-650°C, and the interval time between the casting and the annealing treatment is less than or equal to 3 minutes.

Citation Information

Patent Citations

  • High-energy-storage-density strontium-sodium-niobate-base glass ceramic energy storage material, and preparation and application thereof

    CN105645772A